VD_FINDINFO HC / 2012 / 69 vom 4. Januar 2012 - VD Tribunal cantonal (2012)
MODIFICATIONEN GÉNÉRAL, OBLIGATION D'ENTRETIEN, REVENU HYPOTHÉTIQUE | 179 al. 1 CC, 138 al. 3 let. a CPC (CH), 142 al. 1 CPC (CH), 142 al. 3 CPC (CH), 276 al. 1 CPC (CH)